Towards an ankle-foot orthosis powered by a dielectric elastomer actuator. (June 2021) - Allen, David P.; Little, Ryan; Laube, Joshua; Warren, Jeremy; Voit, Walter; Gregg, Robert D.
Abstract: Foot drop is the inability to dorsiflex the ankle (raise the toes) due to neuromuscular impairment, and this common condition can cause trips and falls. Current treatments for chronic foot drop provide dorsiflexion support, but they either impede ankle push off or are not suitable for all patients. Powered ankle-foot orthosis (AFO) can counteract foot drop without these drawbacks, but they are heavy and bulky and have short battery life. To counteract foot drop without the drawbacks of current treatments or powered AFO, we designed and built an AFO powered by dielectric elastomer actuators (DEAs), a type of artificial muscle technology. This paper presents our design and the results of benchtop testing. We found that the DEA AFO can provide 49 % of the dorsiflexion support necessary to raise the foot. Further, charging the DEAs reduced the effort that would be required for plantarflexion compared to that with passive DEA behavior, and this operation could be powered for 7000 steps or more in actual operation. DEAs are a promising approach for building an AFO that counteracts foot drop without impeding plantarflexion, and they may prove useful for other powered prosthesis and orthosis designs.